A Text Mining Approach to Analyzing the Role of Negative Sentiment Words in News Articles on Suicide and Related Incidents - Selamat Subagio; Samsir Samsir; Abdul Hakim Dalimunthe; Ronal Watrianthos (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study examines the role of negative sentiment words in news media coverage of suicide and related incidents through analysis of 1,515 news articles published between 2019 and 2024. Using advanced text mining techniques and sentiment analysis, we investigated patterns in emotional language use and their impact on public discourse. The research revealed frequent usage of negative sentiment words such as